Rapid Automatized Naming as a Universal Marker of Developmental Dyslexia in Italian Monolingual and Minority-Language Children - Carioti, Desiré; Stucchi, Natale; Toneatto, Carlo; Masia, Marta Franca; Broccoli, Martina; Carbonari, Sara; Travellini, Simona; Del Monte, Milena; Riccioni, Roberta; Marcelli, Antonella; Vernice, Mirta; Guasti, Maria Teresa; et al. (Frontiers in Psychology, 2022)
Rapid Automatized Naming (RAN) is considered a universal marker of developmental dyslexia and could be helpful to identify a reading deficit also in minority language children (MLC) in which it may be hard to disentangle whether the reading difficulties are due to a learning disorder or to lower proficiency in the language of instruction. We tested reading and rapid naming skills in monolingual Good Readers (mGR), monolingual Poor Readers (mPR) and MLC, by using our new version of RAN, the RAN-Shapes, in 127 primary school students (from 3rd to 5th grade). In line with previous research, MLC showed, on average, lower reading performances as compared to mGR. However, the two groups performed similarly to the RAN-Shapes task. Contrarywise, mPR underperformed both in the reading and the RAN tasks. Our findings suggest that reading difficulties and RAN performance can dissociate in MLC; consequently, the performance at the RAN-Shapes may contribute to the identification of children at risk of a reading disorder without introducing any linguistic bias when testing MLC.